50 TAHUN DIBUKANYA KONSILI VATIKAN II. Reformasi dan Restorasi - George Ludwig Kirchberger (Jurnal Ledalero, 2013)
To recall the 50th anniversary of the Second Vatican Council, in the first place the author describes the basic texture of the council, namely its spirit of renewal and dialogue and its emphasis upon the church as the people of God. Then follows a brief response to the event itself leading to questions that remain open, mentioning some four groups of issues that were not settled by the council. The next section looks at some limitations in councilar teaching which made implementation difficult in the post-counciliar period. These include the non-awareness of the council participants of the need for legally binding decree, and the way in which, time and again, mutually contradictory statements are placed side by side in the documents without any attempt to relate the two contrary directions implied. By making use of these two weaknesses, the Roman Curia in particular has tried to neutralise a number of reforms, among others, by recentralising the decision making processes of the Catholic Church. One challenge we face 50 years after the council was openned, is to implement the principle of subsidiarity as well and as intensive as possible, and to recall the most fundamental principle in the Catholic Church, namely that each one must follow their conscience. Therefore, in openness to the gospel and conscious of the signs of the times, the struggle for renewal should take place in constructive non-obedience to efforts for restoration being undertaken in a number of quarters. Kata-kata kunci: awam, dialog, Gereja, Injil, pembaruan, persekutuan, restorasi, umat Allah